2014
DOI: 10.1111/cns.12233
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme 2/Ang‐(1–7)/Mas Axis Protects Brain from Ischemic Injury with a Tendency of Age‐dependence

Abstract: SUMMARY Background The angiotensin (Ang) converting enzyme 2 (ACE2)/Ang-(1-7)/Mas receptor pathway is an important component of the renin–angiotensin system and has been suggested to exert beneficial effects in ischemic stroke. Aims This study explored whether the ACE2/Ang-(1-7)/Mas pathway has a protective effect on cerebral ischemic injury and whether this effect is affected by age. Methods We used three-month and eight-month transgenic mice with neural over-expression of ACE2 (SA) and their age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 40 publications
3
51
0
2
Order By: Relevance
“…Activation of Ang-(1-7)-Mas-R signaling attenuates the development of hypertension and the pathologic progress of atherosclerosis [17,36]. A recent study has shown that neural over-expression of ACE2 lowers neurological deficit scores and leads to smaller stroke volumes following middle carotid artery occlusion-induced stroke in mice [19], suggesting that ACE2 protects the brain from ischemic injury. Also, this study suggests that activation of ACE2/Ang-(1-7)-Mas-R pathways can exert a direct neuroprotective action by alleviating ischemia-induced cell swelling and cell death [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Ang-(1-7)-Mas-R signaling attenuates the development of hypertension and the pathologic progress of atherosclerosis [17,36]. A recent study has shown that neural over-expression of ACE2 lowers neurological deficit scores and leads to smaller stroke volumes following middle carotid artery occlusion-induced stroke in mice [19], suggesting that ACE2 protects the brain from ischemic injury. Also, this study suggests that activation of ACE2/Ang-(1-7)-Mas-R pathways can exert a direct neuroprotective action by alleviating ischemia-induced cell swelling and cell death [19].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that neural over-expression of ACE2 lowers neurological deficit scores and leads to smaller stroke volumes following middle carotid artery occlusion-induced stroke in mice [19], suggesting that ACE2 protects the brain from ischemic injury. Also, this study suggests that activation of ACE2/Ang-(1-7)-Mas-R pathways can exert a direct neuroprotective action by alleviating ischemia-induced cell swelling and cell death [19]. In addition, ICV infusion of Ang-(1-7) or an ACE2 activator reduces ischemic injury in rats that are caused by a reduction in cerebral blood flow [18,31].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are especially relevant from a translational perspective, as systemic treatment infusions were not started until 2 h after stroke. Importantly, the protective effects of the Ang-(1-7)–Mas system in stroke are preserved and may even be enhanced in aged animals [31•]. …”
Section: The Angiotensin-(1-7)–mas Axis and Strokementioning
confidence: 99%
“…7,8 Ang(1-7) counterregulates Ang II actions through activation of the Mas G-protein-coupled receptor, 9,10 and attenuates reactive oxygen species (ROS) partly through decrease in NADPH oxidase (Nox) expression, [11][12][13] which plays a key role in the hypertension-induced ROS generation. 14,15 Thus, ACE2/Ang(1-7)/Mas axis pathway plays a protective role in the cardiovascular system against RAS.…”
Section: Introductionmentioning
confidence: 99%